Reproductive factors and subsequent pregnancy outcomes in patients with prior pregnancy loss - Xin Yang; Fangxiang Mu; Jian Zhang; Liwei Yuan; Wei Zhang; Yanting Yang; Fang Wang (BMC, 2024)
Abstract Background At present, individualized interventions can be given to patients with a clear etiology of pregnancy loss to improve the subsequent pregnancy outcomes, but the current reproductive status of the patient cannot be changed. The aim of this study was to investigate the association between female reproductive status and subsequence pregnancy outcome in patients with prior pregnancy loss (PL). Methods A prospective, dynamic population cohort study was carried out at the Second Hospital of Lanzhou University. From September 2019 to February 2022, a total of 1955 women with at least one previous PL were enrolled. Maternal reproductive status and subsequent reproductive outcomes were recorded through an electronic medical record system and follow-up. Logistic regression was used to evaluate the association between reproductive status and the risk of subsequent reproductive outcomes. Results Among all patients, the rates of subsequent infertility, early PL, late PL, and live birth were 20.82%, 24.33%, 1.69% and 50.77% respectively. In logistic regression, we found that age (OR 1.08, 95% CI 1.04-1.13) and previous cesarean delivery history (OR 2.46, 95% CI 1.27-4.76) were risk factors for subsequent infertility in patients with PL. Age (OR 1.06, 95% CI 1.03-1.10), age at first pregnancy (OR 1.06, 95% CI 1.03-1.10), BMI (OR 1.06, 95% CI 1.02-1.11), previous PL numbers (OR 1.18, 95% CI 1.04-1.57) and without pre-pregnancy intervention (OR 1.77, 95% CI 1.35-2.24) were risk factors for non-live birth. Age (OR 1.06, 95% CI 1.03-1.09), age at first pregnancy (OR 1.06, 95% CI 1.02-1.09), BMI (OR 1.07, 95% CI 1.02-1.11), previous PL numbers (OR 1.15, 95% CI 1.02-1.31) and without pre-pregnancy intervention (OR 2.16, 95% CI 1.65-2.84) were risk factors for PL. Conclusions The reproductive status of people with PL is strongly correlated with the outcome of subsequent pregnancies. Active pre-pregnancy intervention can improve the subsequent pregnancy outcome. Trial registration This study was registered in the Chinese Clinical Trial Registry with the registration number of ChiCTR2000039414 (27/10/2020).